2017
DOI: 10.1155/2017/7830262
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Toll-Like Receptor/Nitric Oxide Signaling Pathway in the Pathogenesis of Cervical Cancer Caused by High-Risk Human Papillomavirus Infection

Abstract: Human papillomavirus (HPV) can activate Toll-like receptor (TLR)/nitric oxide (NO) signaling pathways; however, whether the TLR/NO pathway is involved in cervical cancer caused by high-risk HPV (HR-HPV) remains unclear. In this study, 43 HR-HPV-positive patients with cervical cancer (CC group), 39 HR-HPV-positive patients with a healthy cervix (HR-HPV group), and 33 HR-HPV-negative controls were recruited. NO concentration in cervical canal and expression of inducible NO synthase (iNOS) in cervical tissues wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 33 publications
(40 reference statements)
3
20
0
Order By: Relevance
“…Cervical cancer cells express TLR3 and are therefore one of the target cells of poly(I:C). 14 We examined the cytokine expression profiles of two different HPV-positive cervical cancer cells, HeLa (HPV18+) and Caski (HPV16+), and found that both cervical cancer cells highly expressed IL-6, which is consistent with previous studies. 15 IL-6 is a characteristic cytokine in cervical cancer, which is up-regulated in CIN III and during the tumour stage.…”
Section: Poly(i:c) Promotes the Expression Of Il-6 In Cervical Cancsupporting
confidence: 88%
See 1 more Smart Citation
“…Cervical cancer cells express TLR3 and are therefore one of the target cells of poly(I:C). 14 We examined the cytokine expression profiles of two different HPV-positive cervical cancer cells, HeLa (HPV18+) and Caski (HPV16+), and found that both cervical cancer cells highly expressed IL-6, which is consistent with previous studies. 15 IL-6 is a characteristic cytokine in cervical cancer, which is up-regulated in CIN III and during the tumour stage.…”
Section: Poly(i:c) Promotes the Expression Of Il-6 In Cervical Cancsupporting
confidence: 88%
“…These results suggest that poly(I:C) is involved in the regulation between tumour cells and tumour-infiltrating macrophages in the local microenvironment of cervical cancer.Cervical cancer cells express TLR3 and are therefore one of the target cells of poly(I:C) 14. However, little is known about whether the topical application of poly(I:C) alters the local microenvironment of the tumour, thereby affecting the functional activity of the locally infiltrating immune cells.…”
mentioning
confidence: 99%
“…While most studies using cell lines show an inhibition of the NF-κB pathway, in CIN and cervical cancer, HPV seems to induce the expression of inflammatory cytokines, which correlates with cancer progression [124,125]. A recent study has shown an increase of nitric oxide (NO) and inducible NO synthase (iNOS), which was suggested to be mediated by TLR-induced NF-κB signalling, in cervical samples from HR-HPV-infected patients [133]. Since NO is a critical component of the tumour microenvironment and promotes tumour angiogenesis, as well as tumour cell invasion and metastasis, it has been studied as a possible target for cancer therapy [134].…”
Section: Cellular Innate Immunity and Cancer Progression In Hpv Infecmentioning
confidence: 99%
“…Therefore, TLRs seem to have dual functions in the tumor microenvironment, to the extent that even cancer cells may express those molecules in order to alter immune response and sustain malignant progression [ 3 , 10 ]. Indeed, recently, TLRs were showed to activate the nitric oxide signalling pathway, supporting cervical carcinogenesis [ 11 ].…”
Section: Toll-like Receptorsmentioning
confidence: 99%
“…As a consequence, lower levels are generally associated with a poor prognosis and cancer progression [ 8 , 12 , 13 ]. However, these receptors have also been correlated with malignancy [ 3 , 11 , 14 , 15 ]. TLR4 was found to be overexpressed in human cervical cancer line (HeLa) [ 11 , 14 ] as well as in premalignant and malignant specimens [ 16 ].…”
Section: Toll-like Receptorsmentioning
confidence: 99%